The features and probability forecasting of short–duration heavy rainfall in the Beijing-Tianjin-Hebei region caused by North China cold vortices - Xing, Nan; Zhang, Yingxin; Li, Sang; Dai, Yi; Hao, Cui; Li, Jing; Zhi, Xiefei (Frontiers in Environmental Science, 2023)
Based on hourly station precipitation data and ECMWF ERA5 reanalysis data from 2009 to 2019, this paper explores the temporal variations and spatial distribution of short–duration heavy rainfall (SDHR) induced by North China cold vortices (NCCV) over the Beijing-Tianjin-Hebei (BTH) region, and comparatively analyzes the characteristic of environmental parameters and then choose some predictors to make probability forecasting for short–duration heavy rainfall induced by North China cold vortices. Results show that short–duration heavy rainfall has obviously interannual, monthly and diurnal variations. Areas of high short–duration heavy rainfall frequency caused by North China cold vortices exhibit eastward movement, which generally locate along the mountain areas of the Beijing-Tianjin-Hebei region in the afternoon, and moves to the coastal areas of the Beijing-Tianjin-Hebei region after midnight. In general, short–duration heavy rainfall induced by North China cold vortices mainly occurs in 16:00–21:00 and around 02:00–05:00, showing a delayed peak time and a secondary peak time in recent years. Besides, short–duration heavy rainfall caused by North China cold vortices occurs fewer but more extremely over the northwestern and southern parts of the Beijing-Tianjin-Hebei region, more frequently and extremely over the border area of the Beijing-Tianjin-Hebei region, and more frequently but with moderate intensity over the coastal area of the Beijing-Tianjin-Hebei region. By comparing the distribution characteristics of some physical parameters for three categories of no precipitation, ordinary precipitation, and short–duration heavy rainfall weather induced by North China cold vortices, it is found that moisture and atmospheric instability conditions have great significance for the occurrence of short–duration heavy rainfall caused by North China cold vortices. Probability forecast for short–duration heavy rainfall caused by North China cold vortices is made based on ingredient method and fuzzy logic algorithms. The result shows the products have good performance, further implying the significance of the environmental parameters for forecasting short–duration heavy rainfall caused by North China cold vortices.